Prevention of hate speech crimes: digital versus real-life environment - Averčenko, Elza Līva (Riga Graduate School of Law, 2022)
Extending the use of social media and other digital networks, as well as technology development and the impact of the pandemic have raised the problem of how to prevent hateful speech from occurring. Limitations on hate speech closely correlate with restriction of freedom of speech, therefore balance between the two should be met to ensure both fundamental democratic right on the freedom of speech, as well as to restrict limitations on one’s honour, dignity and safety. To answer whether mechanisms for combating the crimes of hate speech in the digital environment are as effective as they are in a real-life situation, the author analyses the international (United Nations) and Council of Europe related bodies’ views on defining what hate speech is and what are the implications to consider when dealing with hate speech online, then the analysis of current legal framework within the European Union (hereinafter also – the EU) and the Strasbourg mechanism follows in order to grasp the contextual framework and examine existing online and offline hate-speech related case-law. Subsequently, the research describes some of the upcoming regulations (both in Europe and on the national level) for tackling hate speech and its use in the online environment. In conclusion, although the European Court of Human Rights take into consideration and strictly evaluate the characteristics of hate speech in an online environment, self-regulation of online intermediaries is the most effective solution to prevent hate speech under the current legal framework.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Hate speech; Hate crimes; Online social networks; European Court of Human Rights